Detection of alkali and alkaline earth metal ions using birefringence of hyperswollen lamellar phase. Issue 6 (27th January 2023) - Sasaki, Koki; Matoba, Shotaro; Uchida, Yoshiaki; Nishiyama, Norikazu
Abstract : We propose a visual detection method using a hyperswollen lamellar phase without electric amplification. Amphiphiles with an oligo(ethylene glycol) chain can catch alkali and alkaline earth metal ions and amplify to macroscopic birefringence. Abstract : Chemical sensors have targeted various substances. Most sensors electrically amplify signals. Here, we propose a visual detection system that uses a hyperswollen lamellar phase and detects targets in a solution without electric amplification. Amphiphiles with an oligo(ethylene glycol) chain can catch alkali and alkaline earth metal ions and amplify to macroscopic birefringence.